2022
DOI: 10.1073/pnas.2120476119
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac-enriched microprotein mitolamban regulates mitochondrial respiratory complex assembly and function in mice

Abstract: Emerging evidence indicates that a subset of RNA molecules annotated as noncoding contain short open reading frames that code for small functional proteins called microproteins, which have largely been overlooked due to their small size. To search for cardiac-expressed microproteins, we used a comparative genomics approach and identified mitolamban (Mtlbn) as a highly conserved 47-amino acid transmembrane protein that is abundantly expressed in the heart. Mtlbn localizes specifically to the inner mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…In the past decade, SEP identification has changed from accidental discovery to high‐throughput screening, thus finding more critical functional SEPs. Figure 3 summarized the history of high‐throughput identification of SEPs in different species [8, 1012, 2930, 3871] and several representative SEPs with important biological functions [5, 14, 16, 1821, 36, 7291].…”
Section: Analysis Strategies and Methodologies Of Sepsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, SEP identification has changed from accidental discovery to high‐throughput screening, thus finding more critical functional SEPs. Figure 3 summarized the history of high‐throughput identification of SEPs in different species [8, 1012, 2930, 3871] and several representative SEPs with important biological functions [5, 14, 16, 1821, 36, 7291].…”
Section: Analysis Strategies and Methodologies Of Sepsmentioning
confidence: 99%
“…The history of high‐throughput identification of SEPs in different species by Ribo‐seq [29, 3471] and MS‐based proteomics [8, 1012, 33, 3856], and representative functional SEPs [5, 14, 16, 1821, 36, 7291]…”
Section: Analysis Strategies and Methodologies Of Sepsmentioning
confidence: 99%
“…And do such second ORFencoded proteins have any physiological functions, with ORF2p as a precedent? Although several lines of evidence suggest that translation of polycistronic mRNAs, some of which encode "microproteins", occurs more frequently than expected in eukaryotes (Kondo et al, 2007;Brubaker et al, 2014;Karginov et al, 2017;Makarewich et al, 2022), further proteomic studies and functional validation of these products will be needed to elucidate these questions.…”
Section: L1 Retrotransposition Cycle and Host Factors That Facilitate...mentioning
confidence: 99%
“…A correlation of Stmp1 with innate immunity was also reported: Stmp1‐deficient macrophages were compromised for the NOD‐like receptor 3 (Nlrp3) inflammasome formation accompanied by a reduction in expression of cleaved Caspase‐1 and IL‐1β at protein levels, suggesting a role of Stmp1 in the activation of the inflammasome but not the priming process [73]. In addition, a recent study reported that cardiac‐specific overexpression of Stmp1 in mice induced cardiomyopathy [72]. These evidence indicates a key role for Stmp1 in diverse physiological functions.…”
Section: Representative Mlps and Their Functionsmentioning
confidence: 99%
“…Except for Stmp1, the origin gene 1810058I24Rik was also predicted to translate into other non-AUG peptides [71]. Stmp1 was also reported to interact with other subunits of CIII [72]. In the mouse heart, its inactivation altered CIII assembly dynamics, reduced CIII activity, and resulted in an altered metabolite profile; while overexpression of Stm-p1 caused increased oxidative stress and mitochondrial dysfunction [72].…”
Section: Stmp1mentioning
confidence: 99%